Novel exposed and buried Au plasmonic grating as efficient sensors. Issue 4 (4th July 2022) - Iqbal, Tahir; Tabassum, Huma; Afsheen, Sumera; Ijaz, Mohsin
Abstract : The exposed and buried gratings of gold (Au) have been simulated to investigate the excitation of surface plasmon polaritons (SPPs) using COMSOL multi-physics-RF module for their application in sensing industry. While investigating the geometrical parameters of grating, the period of the grating structure (i.e. 700 nm) as well as the thickness of grating film (50 nm) was held constant when slit width has been optimized as 500 and 100 nm for exposed and buried grating, respectively. The normal transmission spectra have been used to evaluate the dip indicating resonance wavelength in transmission as well as reflection spectra. The buried grating device found to be a more efficient sensing device, having a sensitivity of 716 nm/RIU, as compared to the exposed grating device with a sensitivity of 674 nm/RIU which reveals the fact that the buried grating offers less scattering to the excited Surface Plasmon Polariton on the grating structure. It is highly fascinating to report that, in the case of buried grating, the sensitivity of the device is increased, and it leads to reduction of the scattering of the surface plasmon polaritons (SPPs). Such a buried structure is novel in sense of nano-grating, hence easier to fabricate finding application as efficient sensors. GRAPHICAL ABSTRACT: UF0001